O trabalho do agente comunitário de saúde na estratégia saúde da família: encontros e desencontros de uma prática em São Carlos/SP - Vieira, Kátia Cristina dos Santos (2014)
This is a descriptive study with qualitative approach, more specifically a case study. It aims to analyze the work of Community Health Agent (ACS), from the perspective of health user and ACS itself, identifying the activities undertaken by these actors, perceptions of ACSs about his role on the team for the individual and collective care assitence, and the perceptions and expectations of users regarding the work of the ACS. The subjects were six ACSs from a unit of Family Health Program of city São Carlos, and four users of the health service and spokesman in the Local Health Council. Theoretical frameworks that supported this study and who were the object of theoretical study: family health, work and health care directives of the Brazilian Unified Health System (SUS).The research technique chosen for data collection was individual semi-structured interviews and data analysis used the technique of thematic analysis. The data collected with ACS and users were analyzed separately and yielded on the following categories: what is to be ACS: between the ideal and the real; organization of daily work of the ACS; demotivation and impotence in the face of adversity; lack of Permanent Education in Health: choking the work of ACS; who is the ACS to me; the real and the ideal work of ACS, and a user's perspective; the effort to strengthen the work of ACS. The results of this study allowed an approximation of the difficulties and easiness from everyday work of the ACS, sometimes demotivating elements, sometimes augmenting the practice of this worker. It was possible to identify the multifunctionality of ACS as one reason for the loss of identity from that worker before the population. As for users, the expectation that the ACS contributes to citizenship, advising people of their rights and duties, ie, not limited in their speeches to the technical work of the ACS was found, but contemplated the political and social dimension in the role of this worker. Research indicates that the change in the health production model depends not only on a worker-ACS- neither simple deployment of new family health teams. A joint effort of all health workers and a critical-reflective analysis of their own practices, reverberating effective change in health production and consolidation of SUS.